A Systematic Review and Meta-analysis of Functional Shoulder Impairment After Latissimus Dorsi Breast Reconstruction. Issue 1 (January 2019) - Steffenssen, Mia C. W.; Kristiansen, Ann-Louise H.; Damsgaard, Tine E.
Abstract : Purpose: The latissimus dorsi flap (LDF) is a very reliable flap and may be used for a multitude of reconstructive purposes. It is widely used for breast reconstruction when performed. It has few complications, except for a possible impact on shoulder function. The aims of this study were to evaluate the validity of the literature by investigating the level of evidence and to perform a meta-analysis. Methods: A systematic literature search was conducted using the databases PubMed, Scopus, and Web of Science. Predictor variables were shoulder function after breast reconstruction with the LDF. Articles were chosen according to 4 different outcomes: shoulder range of motion (ROM), shoulder strength, DASH score, and subjective evaluation. Results: Twenty-six articles were found, including 1045 patients: 8 level II, 16 level III, 1 level IV, and 1 level V articles. The meta-analysis showed that both ROMs for flexion and abduction are significantly impaired at less than or at 3 months of follow-up. Conclusions: There are several influencing factors, such as age, smoking, obesity, radiotherapy, and physiotherapy. Moreover, the impact on shoulder function seemed influenced by the type of thoracodorsal vessel–based flap. From the level of evidence analysis, there is a tendency that the LDF transfer does affect shoulder function. This limitation seems to be minimal, and few patients experience a major impact on shoulder function. However, the existing literature on total shoulder impairment after breast reconstruction with LDF is insufficient to draw any final conclusion. There is a need for future studies and current articles that suggest that the initial measurement should be performed preoperatively (preferably at the time of diagnosis or initial biopsy) and follow-ups with measurements at 6, 12, and 24 months (long-term effect) after surgery. We recommend measurements of both operated and nonoperated sides. Each measurement should be accompanied by a history with special emphasis on shoulder function. The methods of measuring outcomes of recommendation are DASH score, ROM with use of a goniometer preferably by a physiotherapist or a health care professional trained by a physiotherapist, and strength measured by, for example, a handheld dynamometer.